SINDROME DE DUBOWITZ - Haddad Júnior, Vidal [UNESP]; Lima Dillon, N. [UNESP] (My University, 1995)
A presentation of two cases of Dubowitz syndrome in monozigous twin girls. The syndrome is a rare congenital disorder, the main clinical aspects of which include retarded intrauterine and post-natal growth, microcephaly, peculiar face and an eczemic rash, resulting from photosensitivity of the regions exposed to sunlight.
Dubowitz syndrome
Keywords: disorders; genetics, medical; photosensitivity; skin diseases, genetic; case report; developmental disorder; female; human; human tissue; monozygotic twins; preschool child